(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The use of artificial intelligence in medicine raises many legal issues. This essay examines how medical AI intersects with the right to informed consent and the principle of self-determination. The author highlights that the complexity and opacity of machine learning could dissuade the patient from consenting AI treatment and, therefore, induce him to give up the benefits that this technology usually brings to his health. Consequently, the author suggests adjusting the content of the information due to the patient, taking into account the limited knowledge that ordinary people have about artificial intelligence, and, more generally, redefining the boundaries of the principle of informed consent.